(untitled) (Terr@ Plural, 2021)
As a new tourist approach, aiming at the valorization of nature elements, particularly the abiotic ones, geotourism is based on the recognition of areas with significant value (intrinsic, scientific, didactic, tourist, aesthetic, economic, and cultural), that give specificities to the place. We present a survey of the geological and geomorphological potentialities of waterfalls in the municipality of São João da Serra for the development of local geotourism. Eight waterfalls were inventoried: Quebra Anzol, Contente, Lau, Boa Vista, Cachimbo, Clemência, Boa Nova, and Deus Dará, all with unique beauty and value whose sustainable exploitation could contribute to the generation of income and employment for the community. However, there are no government actions aimed even at the installation of access roads to most of the identified waterfalls.